Application of glycyrrhizinic acid in treatment of patients with alcoholic liver disease - I. G. Nikitin; I. Ye. Baykova; V. M. Volynkina; L. M. Gogova; G. I. Storozhakov; M. P. Prushkovskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate of clinical efficacy and safety profile of parenteral form of «Phosphogliv» preparation containing glycyrrhizin and essential phospholipids, at treatment of patients with alcoholic liver disease.Materials and methods. Overall 106 patients with chronic alcohol-induced liver diseases were investigated, diagnosis was verified by standard methods with obligatory assessment of the expert in narcology. Patients were randomized by random sample method in two groups: I group (n=58) – an abstinence in combination to placebo (intravenous injection 20 ml of normal saline solution 2 times per week), II group (n=48) – abstinence in combination to intravenous injection of 2,5 g of phosphogliv 2 times per week. Total period of observation was 104–106 wks on the average. Basic biochemical parameters, liver morphology and data of US-investigation were estimated.Results. Before treatment the level of transaminases was: ALT 89,3±12,9 IU/l and AST 124,3±26,7 IU/l (I group), 78,2±23,8 and 135,6±37,3 IU/l respectively (II group). On the 52-nd week levels of transaminases essentially differed: ALT level at patients of the I group became 84,6±10,4, at patients of II group – 39,7±12,5 IU/l, AST – respectively 96,6±11,7 and 63,2±9,6 IU/l (p<0,01). The level of tumor necrosis factor-α significantly differed and was equal to 796,8±89,9 mcmol/l in patients receiving placebo, and 412,8±76,8 mcmol/l in group, receiving glycyrrhizinic acid (p><0,01). Conclusion. Application of phosphogliv along with abstinence increases efficacy of therapy of alcoholinduced liver disease. The further studying of this agent is necessary at various clinical variants of disease with dynamic evaluation of basic clinical and laboratory parameters and effects of treatment on liver morphology.>< 0,01). The level of tumor necrosis factor-α significantly differed and was equal to 796,8±89,9 mcmol/l in patients receiving placebo, and 412,8±76,8 mcmol/l in group, receiving glycyrrhizinic acid (p< 0,01).Conclusion. Application of phosphogliv along with abstinence increases efficacy of therapy of alcoholinduced liver disease. The further studying of this agent is necessary at various clinical variants of disease with dynamic evaluation of basic clinical and laboratory parameters and effects of treatment on liver morphology.